Digital Surrealism: Video Game Space - Gündüz, Esra Nur; Özener, Ozan Önder (Istanbul Technical University, 2024)
The concept of virtual reality (VR), perceived as a copy of physical reality, restricts both the creators and users of the space, leaving no room for potential surreal experiences. The main motivation for conducting the research on virtual surreal space is to open up creative/productive spatial possibilities for discussion from a thought perspective that goes beyond this definition. Although there are various approaches to digital space in the literature, these studies mostly rely on computational methods. In contrast, this study aims to explore space from the perspective of "digital surrealism" which is ignored in spatial studies, through the computer-based gaming experience. Scholars writing about architecture and surrealism have argued that, unlike other forms of fine art, architecture was never an integral part of surrealism. Against this perspective of the digital game experience, the study aims to question whether it is possible to interpret the space with a surreal perspective and to investigate whether the space can approach surrealist thought with the digital game experience fed by computational methods that support the concepts of 'autonomy' and 'ubiquity'. The main goal of the study is to explore the relations between surrealism and architecture and the spatial potential of these relations through the experiences of the players. The surrealist spatial potential of digital space experience is explored in Superliminal (2019), a puzzle game that transforms the experience into allegories of dreams, free-thinking and multiple opportunities. Data analysis performed on the STEAM platform and the First Manifesto of Surrealism (1924), in which surrealism came into existence as a movement, were analyzed with Python software. The experimental group's thoughts and comments expressed on the STEAM platform were analyzed. Preliminary results of the study are presented with the "regression tree" method. Using the Python programming language, analyses are prosuded to discuss game spaces from a lens of surrealism perspective.
Keywords: Artificial Reality; Mimari Bilim ve Teknoloji; Digital surrealism; Surrealism; Video game space; Spatial experience.; Dijital sürrealizm; Sürrealizm; Video oyun mekanları; Mekansal deneyim; Architectural Science and Technology; Sanal Gerçeklik